Development of a strategic supply chain positioning methodology for SMEs in Singapore - Lim Yan Guan, Roland (Cranfield University, 2007)
The Small and Medium Enterprises (SMEs) in Singapore face particular challenges from increasing competition from manufacturers in China, India and other East Asian countries. For these SMEs, survival and growth depend critically on defining their own competitive space among other companies in the manufacturing supply chains. Unfortunately there is little previous research on Strategic Supply Chain Positioning (SSCP) with most current frameworks and methodologies being developed from the perspective of the larger multinational companies (MNCs). Therefore this research has set out to develop a practical and robust SSCP methodology to support strategic decision making in SMEs in Singapore. The research programme began with a review of the existing methodologies and selecting the most promising methodology for further evaluation. Testing of this methodology was then carried out through four industrial case studies. Based on the results of the evaluation, the methodology was refined and a pilot SSCP methodology for SMEs was developed. Further testing was then carried out with another four case studies to identify particular characteristics for further improvement. The final SSCP methodology was then developed as a computerised software tool and presented in Chapter 9 of this thesis. The research has created a strategic supply chain positioning methodology that provides practical and procedural aid for strategic supply chain positioning efforts for SMEs in Singapore. This methodology guides the practitioner through a series of well-defined steps necessary to define the desired strategic positioning of the company in the supply chain. Such a methodology has been lacking in previous research and, hence, is the main contribution to knowledge in this thesis.